First-principles study of point defects in thorium carbide - Perez Daroca, Diego Raul (2014)
Thorium-based materials are currently being investigated in relation with their potential utilization in Generation-IV reactors as nuclear fuels. One of the most important issues to be studied is their behavior under irradiation. A first approach to this goal is the study of point defects. By means of first-principles calculations within the framework of density functional theory, we study the stability and formation energies of vacancies, interstitials and Frenkel pairs in thorium carbide. We find that C isolated vacancies are the most likely defects, while C interstitials are energetically favored as compared to Th ones. These kind of results for ThC, to the best authors’ knowledge, have not been obtained previously, neither experimentally, nor theoretically. For this reason, we compare with results on other compounds with the same NaCl-type structure.